Quantitative Autofluorescence Imaging of A375 Human Melanoma Cell Samples: A Pilot Study - Shirkavand, Afshan; Mohajerani, EzeddinÂ; Farivar, Shirin; Ataie-Fashtami, Leila; Ghazimoradi, Mohammad Hossein (Journal of Lasers in Medical Sciences, 2021)
Introduction: Skin cancer is one of the most common types of malignancy worldwide. Human skin naturally contains several endogenous fluorophores, as potential sources that can emit inherent fluorescence, called intrinsic autofluorescence (AF). The melanin endogenous fluorophore in the basal cell layer of the epidermis seems to have a strong autofluorescence signal among other ones in the skin. This pilot study aimed to investigate the feasibility of the detection of autofluorescence signals in the A375 human melanoma cell line in the cell culture stage using the FluoVision optical imaging system. Methods: The human skin melanoma cell line (A375) donated as a gift from Switzerland (University Hospital Basel) was cultured. For the imaging of the A375 human melanoma cell sample in this pilot study, the FluoVision optical imaging device (Tajhiz Afarinan Noori Parseh Co) was applied. The proposed clustering image processing code was developed based on the K-mean segmentation method, using MATLAB software (version 16). Results: The quantification of color pixels in the color bar along with the intensity score of the autofluorescence signal ranged between 0 and 70 was written in the image processing code execution and a threshold higher than 40%, proportional to the ratio of autofluorescent cells. The percentage of the signal of A375 autofluorescent melanoma cells in the 3 studied cell samples was calculated as 3.11%±0.6. Conclusion: This imaging method has the advantage of no need for fluorophore labels over the existing fluorescence imaging methods, and it can be regarded as one of the important choices of label-free imaging for this A375 melanoma cell line containing the intrinsic endogenous fluorophore in cell studies. DOI: 10.34172/jlms.2021.04